Aportaciones de la platería leonesa del siglo XVI en el principado de Asturias (Estudios humanísticos. Geografía, historia y arte, 1992)
The activity of the silversmith of León dureing the 16th. century is well known because of the presence of Enrique de Arfe, orginating in German. Asturias, the region situated on the north of León, also recieved the influence of the good level of the silvesmith work of León. We conserve in Asturias several pieces manufactured by the silversmiths of León in this century, such as Enrique de Arfe, Andrés Rodríguez, Juan de Herrera, Gerónirno Hernández and Juan Pacheco. The most representative work is the four screptres of the Cathedral of Oviedo, made in Enrique de Arfe's workshop in 1527. We conserve the document of the contract in the Cathedral archives. Here I presente 7 pieces of León's work of this century and the list of the marks used by the silversmiths aboye mentioned.